Digalactoside expression in the lipopolysaccharide of haemophilus influenzae and its role in intravascular survival - Griffin, R.; Bayliss, Christopher D.; Herbert, Mark A.; Cox, Andrew D.; Makepeace, Katherine; Richards, J.C.; Hood, Derek W.; Moxon, E. Richard (ASM Press, 2005)
Digalactoside (gal-1-4 gal) structures of the lipopolysaccharide (LPS) of Haemophilus influenzae are implicated in virulence. A confounding factor is that tetranucleotide repeats within the lic2A, lgtC, and lex2 genes mediate phase-variable expression of the digalactosides. By deleting these repeats, we constructed recombinant strains of RM153 constitutively expressing either one or two LPS digalactosides. Expression of two digalactosides, rather than one, was associated with increased virulence of H. influenzae in vivo.